EFEKTIVITAS KEPUASAN SISTEM INFORMASI MANAJEMENT KLINIK PRATAMA HASNA DENGAN MENGGUNAKAN METODE END USER COMPUTING SATISFACTION ( EUCS) - raafi puja; Bajeng Nurul Widyaningrum; Lutfiyah Rizqulloh (MEDIKA TRADA, 2025)
Digital transformation in the health sector requires health service facilities to implement efficient and responsive information systems. Hasna Pratama Clinic as a primary clinic in Semarang City has implemented the Clinic Management Information System (SIM Klinik) since 2024, but its implementation has not been optimal. This study aims to analyze the effectiveness of SIM Clinic user satisfaction using the End User Computing Satisfaction (EUCS) approach. The assessment was carried out on five dimensions of content, accuracy, format, ease of use, and timeliness. A qualitative descriptive approach was used through in-depth interviews and direct observation of health workers. The results of the study indicate that in general the system is considered quite good in terms of ease of use and display efficiency, but is still weak in terms of data integration, medical history, and system stability. These findings provide an important contribution to the development of more effective information systems in primary health care. Keywords: Clinical SIM, User Satisfaction, EUCS, Electronic Medical Record, Health Information System